The activity pattern of barn owls in urban area as biological control agents of rats - Mohd Hamdan, Muhammad Hazziq (2017)
Barn owl has been established as a biological control agent of rats in oil palm plantations and rice fields. In view of the serious rodent infestation in urban areas, an initiative has been launched to introduce barn owl in a city environment. Serdang has been designated for the pioneer project of the barn owls release for this purpose. To investigate the ranging and foraging activity of the barn owl, radio telemetry is employed. The objective is to draw up the activity pattern of the barn owl in a city perimeter. The activity pattern of male and female over a time period will be investigated. Two females will be tagged with radio transmitters and followed from 1800 hours to 0600 hours daily for a total of ten days until sufficient radio locations obtained. If the owls remain in the same area, the activity patterns will be compared from month to month dictated by circumstances. The locations of the owls will be determined at hourly intervals or for as frequent as possible over the night. The distance travel from one radio locations to the next is a measure of the level of activity for the respective hourly interval. The mean distance moved over several nights indicates the level of activity for each hourly interval. The Biotas software will be used to analyse home ranging parameters of each owl and the nightly activity profile. It is anticipated that males are more active since they engaged in more exploratory foraging behaviour.